Clonal hematopoiesis of indeterminate potential associates with higher risk of thromboembolism in severe COVID-19 - Gregorio Maria Bergonzi; Jacques-Emmanuel Galimard; Federico Mario Aletti; Piera Angelillo; Sara Mastaglio; Federico Erbella; Diego Palumbo; Giliola Calori; Patrizia Rovere Querini; Cristina Tresoldi; Gabriele Fragasso; Francesco De Cobelli; et al. (Haematologica)
Not available.